2015
DOI: 10.1016/j.jvs.2014.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of persistent intraoperative type Ia endoleak after standard endovascular aneurysm repair

Abstract: Despite adjunctive intraoperative maneuvers, persistent type Ia endoleaks can be relatively common. Our study indicates that they may be observed in selected patients. Further research is required to investigate the natural course and management of type Ia endoleaks identified intraoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 24 publications
(26 reference statements)
3
37
1
Order By: Relevance
“…The initial completion arteriogram identified 44 of 209 patients with type Ia endoleaks, with 33 patients (75%) having a persistent endoleak even after intraoperative adjunctive procedures were performed, which included repeat balloon angioplasty, aortic cuff extension, and Palmaz stent (Cordis) placement. 29 Eleven patients had successful treatment of the type Ia endoleak during the initial EVAR procedure, and there was no evidence of recurrent endoleak in these patients during a median follow-up of 27 months. For those 33 patients with persistent type Ia endoleaks, in spite of attempts at repair during the initial EVAR procedure, 31 showed spontaneous resolution of the endoleak on the first surveillance evaluation using CTA, resulting in a 94% spontaneous resolution.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The initial completion arteriogram identified 44 of 209 patients with type Ia endoleaks, with 33 patients (75%) having a persistent endoleak even after intraoperative adjunctive procedures were performed, which included repeat balloon angioplasty, aortic cuff extension, and Palmaz stent (Cordis) placement. 29 Eleven patients had successful treatment of the type Ia endoleak during the initial EVAR procedure, and there was no evidence of recurrent endoleak in these patients during a median follow-up of 27 months. For those 33 patients with persistent type Ia endoleaks, in spite of attempts at repair during the initial EVAR procedure, 31 showed spontaneous resolution of the endoleak on the first surveillance evaluation using CTA, resulting in a 94% spontaneous resolution.…”
Section: Discussionmentioning
confidence: 88%
“…In another recent study by Millen and associates, 29 94% of patients with type Ia endoleaks found on completion arteriography after standard EVAR had endoleaks that resolved spontaneously. The initial completion arteriogram identified 44 of 209 patients with type Ia endoleaks, with 33 patients (75%) having a persistent endoleak even after intraoperative adjunctive procedures were performed, which included repeat balloon angioplasty, aortic cuff extension, and Palmaz stent (Cordis) placement.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Two-year follow-up results on 36 patients showed no AAA rupture, stent fracture or migration, and no type I, III, or IV endoleak. Type II leak was noted in 33 % of patients, with associated sac enlargement in only one patient [21].…”
Section: Device Planningmentioning
confidence: 96%
“…In one study, adjunctive procedures such as repeated balloon inflation or addition of a cuff or Palmaz stent (Cordis, Miami Lakes, FL, USA) were shown to resolve the leak only 25 % of the time. However, on follow-up CTA, 94 % of these patients had resolution of the leak [21]. Determining which patients with type I leak do not need further intervention at the end of the procedure needs further study.…”
Section: N/a Secondary Endograft or Explantmentioning
confidence: 99%